Clinical Correlation of Ovarian Cyst Malignant or Benign with Ultrasound Reports - Din Muhammad Sohu, Inayatullah, Muhammad Rashid Rasul, Akhtar Hussain Phul, Imran Khan Memon, Rabia Hafeez (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To investigate clinical correlation of ovarian cyst malignant or benign with ultrasound reports. Study Design: Prospective observational study Place and Duration of Study: Department of Radiology, Ghulam Muhammad Mahar Medical College, Sukkur from 1st November 2019 to 31st July 2021 Methodology: Ninety five patients with accidental diagnosis of ovarian mass were enrolled as patients and had symptoms of abdominal pain, palpable-mass as well as irregularities in the menstrual cycles. Diagnosis of each patient was based on ultrasound which was assisted with TVS or Doppler depending upon the cases under consideration. The ultrasonographical reports were correlated with the clinical examination and diagnosis findings for better assessment of the ovarian mass. Results: Mean age was 42 years with 62.3% those women who were in reproductive age while rest were having menopause. 70% were presenting abdominal pain and 2% were asymptomatic. Doppler scan reports showed that all cases of malignancy were having high vascularity with R1< 0.4 in 100% of cases while R1>0.4 was highest in benign cases. The ultrasonographical imaging showed an obvious variance in the imaging reports of benign verses malignant cases where an irregular margin mass was prominently noticeable in cases of malignant ovarian tumor. Conclusion: High sensitivity and specificity was also seen among clinical cases correlated with ultrasound having Doppler scanning.